Quality of Life Outcomes of Transoral Robotic Surgery With or Without Adjuvant Therapy for Oropharyngeal Cancer - YUMUŞAKHUYLU, ALİ CEMAL (WILEY, 2018)
Objectives/Hypothesis: To compare quality of life (QOL) of patients who underwent transoral robotic surgery (TORS) alone, with adjuvant radiation therapy (RT), or adjuvant chemoradiation therapy (CRT) in the treatment of oropharyngeal squamous cell cancer (OPSCCA). Study Design: Prospective cohort study. Methods: Medical records were reviewed for 111 patients treated for OPSCCA from 2008 to 2015. Patients were administered the Head and Neck Cancer Inventory (HNCI) to evaluate QOL preoperatively, and at 3 weeks, 3 months, 6 months, and 1 year postsurgery. QOL data were compared between 13 patients treated with TORS alone, 31 with adjuvant RT, and 67 with adjuvant CRT by a linear mixed effects model. Results: Mean follow-up was 35 months. The HNCI response rates at 3 weeks and 3, 6, and 12 months were 80%, 60%, 55%, and 46%, respectively. TORS alone reported significantly higher eating scores than adjuvant RT or CRT at 3 and 6 months, and higher speech scores compared to adjuvant CRT at 3 months and adjuvant RT at 6 months. TORS alone and adjuvant RT reported less social disruption compared to adjuvant CRT at 3 months. Adjuvant CRT had consistently lower overall QOL scores until 6 months. No TORS-alone patient required percutaneous endoscopic gastrostomy, and no study patient required tracheostomy during treatment. Conclusions: TORS alone maintained higher QOL than adjuvant RT or CRT in eating, social function, speech, and overall QOL postsurgery. QOL and functional metrics were better for 6 months in TORS-alone patients, and at 12 months, the differences were not significant.
Keywords: Transoral robotic surgery; oropharyngeal cancer; quality of life; adjuvant therapy; NECK-CANCER; RADIATION-THERAPY; HEAD; CHEMORADIATION; DISORDERS; IMPACT; TORS